Հունաստանի պատկերը ԺԷ-ԺԸ դարերի հայկական պատկերացումներում - Բոզոյան, Ազատ
Greece has accompanied the Armenian history and culture for centuries. It has left its influence on numerous layers of the Armenian mentality. Let us try to arrange all the phenomena of the cultural history, which have their influence on the Armenian conception of the 17th and 19th centuries. Archaeological, historical-philological and linguistic works and studies will serve as material for the research of conceptions, which have centuries-old basis and are compared to present way of thinking. В течении веков Греция имела свое неоисредственное влияние на историю Армении и ее культурное наследие. Это обстоятельство сыграло свою роль на формирование менталитета разных социальных слоев армянского общества. В нашей статье мы попробывали восстоновить некоторые аспекты армяно-греческого культурного взаимовлиянии на протяжении 17 – 19-х веков.
Keywords: Պատմություն; Մշակույթ